Environment in the Courtroom - Ingelson, Allan E. (University of Calgary Press, 2019)
Canadian environmental law is a dynamic and exciting area that is playing an increasingly important role in furthering sustainable development policy. Environmental law has distinctive relevant principles, operating procedures, implications, and importance in comparison with other areas of law, and these distinctions must be appreciated both within the legal community and by all those who are concerned with the way that courts handle environmental cases. Environment in the Courtroom provides extensive insight into Canadian environmental law. Covering key environmental concepts and the unique nature of environmental damage, environmental prosecutions, sentencing and environmental offences, evidentiary issues in environmental processes and hearings, issues associated with site inspections, investigations, and enforcement, and more, this collection has the potential to make make a significant difference at the level of understanding and practice. Containing perspective and insight from experienced and prominence Canadian legal practitioners and scholars, Environment in the Courtroom addresses the Canadian provinces and territories and provides context by comparison to the United States and Australia. No other collection covers these topics so comprehensively. This is an essential reference for all those interested in Canadian environmental law.